Coding Semantic Relationships for Medical Bibliographic Retrieval: A Preliminary Study - Powsner, Seth M. (1987)
The coding of semantic relationships may permit more precise searches of the medical literature than conventional key/index term coding with boolean operators for retrieval. Such semantic coding captures the distinction between papers concerned with how hepatitis B (HB) may cause/predispose to liver neoplasms (LN) and papers concerned with how HB may affect outcome in patients with LN. These distinctions were demonstrated by retrieving sets of MEDLINE (National Library of Medicine) abstracts, each set relevant to two clinical terms. Each abstract was then reviewed to determine the implied semantic relationship(s) between the two terms. Even in the restricted realm of liver diseases a number of very different relationships between terms are addressed in the literature. In addition, coding “no relationship” allows articles discussing LN and HB independently to be avoided. Semantic relationship coding may prove to be very helpful for retrieving concise reference lists to support clinical decisions.